Rethinking urban quality of life: Unveiling causality links using cognitive mapping, neutrosophic logic and DEMATEL - Vaz-Patto, C.; Ferreira, F.; Govindan. K.; Ferreira, N. (European Journal of Operational Research, 2024)
Quality of life (QoL) is an important issue that reflects changes around the world caused not only by human population density, growth, and related initiatives but also by crises and pandemics. Concurrently, people’s increasing tendency to live in urban areas has generated growing concerns about correctly assessing city QoL to facilitate the implementation of practical measures that favor both current and future generations’ well-being. Conducting accurate analyses in this context is a challenging endeavor due to the subjectivity and complexity intrinsic to QoL evaluations. Thus, this study develops a multicriteria model based on a constructivist and complementarity logic that helps decision makers evaluate urban QoL. The proposed analysis system combines cognitive mapping, neutrosophic logic, and the decision-making trial and evaluation laboratory (DEMATEL) method in order to address the limitations of previous studies. This model also enhances experts’ ability to decide which determining factors should be included in assessments of urban QoL. In addition, the system developed can help decision makers cope with uncertainty during evaluations because this holistic, realistic, and complete model fosters conscious decision making in urban contexts. The practical implications, advantages, and limitations of the proposed analysis system are also discussed.